The Multifaceted Role of Regulatory T Cells in Breast Cancer - Kos, Kevin; de Visser, Karin E (Annual review of cancer biology, 2021)
The microenvironment of breast cancer hosts a dynamic cross talk between diverse players of the immune system. While cytotoxic immune cells are equipped to control tumor growth and metastasis, tumor-corrupted immunosuppressive immune cells strive to impair effective immunity and promote tumor progression. Of these, regulatory T cells (T ), the gatekeepers of immune homeostasis, emerge as multifaceted players involved in breast cancer. Intriguingly, clinical observations suggest that blood and intratumoral T can have strong prognostic value, dictated by breast cancer subtype. Accordingly, emerging preclinical evidence shows that T occupy a central role in breast cancer initiation and progression and provide critical support to metastasis formation. Here, T are not only important for immune escape but also promote tumor progression independent of their immune regulatory capacity. Combining insights into T biology with advances made across the rapidly growing field of immuno-oncology is expected to set the stage for the design of more effective immunotherapy strategies.